The synergistic effect of diabetes mellitus and low high-density lipoprotein cholesterol on the prediction of pneumonia in peritoneal dialysis patients: a multicenter retrospective study - Shang, Sijia; Zhang, Xing; Zhan, Xiaojiang; Tian, Na; Wen, Yueqiang; Wang, Xiaoyang; Feng, Xiaoran; Zhou, Qian; Wu, Xianfeng; Xu, Qingdong; Shi, Guojun; Zheng, Yijia; et al. (Frontiers in Nutrition, 2026)
BackgroundPatients undergoing peritoneal dialysis (PD) often exhibit abnormal glucose and lipid metabolism. Pneumonia is an important infectious complication in PD patients. Diabetes mellitus (DM) and low levels of high-density lipoprotein cholesterol (HDL-C) are risk factors for pneumonia. This study aimed to investigate the relationship between the co-existence of DM and low HDL-C and the occurrence of pneumonia in PD patients.MethodsThis multicenter retrospective study was conducted across five PD centers from January 1, 2008, to December 31, 2020. The primary outcome was new-onset pneumonia. Patients were divided into four groups based on the presence of DM and low HDL-C. Cox regression analysis was performed to evaluate the association between the co-existence of DM and low HDL-C and the development of pneumonia.ResultsA total of 1,293 PD patients were included in this study. During a median follow-up period of 53 months, pneumonia occurred in 137 patients (10.6%). Multivariable Cox regression analysis demonstrated that patients with coexisting DM and low HDL-C had a significantly increased risk of pneumonia compared to those without either condition (HR = 2.252, 95% CI, 1.232–4.115). Consistent results were observed in subgroup analyses stratified by age, sex, and smoking history.ConclusionThe concurrent assessment of DM and low HDL-C may help identify high-risk individuals for pneumonia and guide the management strategies for PD patients.